Avaliação de fala de usuários de implante coclear após ensino de relações modelo articulatório/figura e palavra falada/figura - Oliveira, Sabrina Roberta (2013)
Cochlear implants have been effective on cases of deep hearing loss, by allowing sound perception. People with prelingual deafness must learn hearing skills, when using this implant. This study is part of a research program on the development of speech comprehension. Goals were, regarding a sample of four children using cochlear implant: using matching-to-sample model, to teach them conditional relations among articulatory model and figures (AC), dictated words and figures (BC); to verify the effects of these relations on new emerging ones (CA, CB, AB and BA), and also on figures naming, echoic behavior and lip reading skills. Multiple baseline design was used with two participants in order to assess teaching outcomes. Participants performance was also assessed via tasks involving copying and selecting, as well as their auditory and expressive abilities. In order to control teaching tasks sequence effects, half of participants were taught AC followed by BC, and the other half BC followed by AC. Participants learned eight trained conditional relations (four ACs and four BCs) and learning was more effective on BC/AC sequence. Participants formed equivalent stimuli classes, which included figures, dictated words and articulatory models. Three participants have demonstrated a better performance on echoic behavior tasks. In selecting and copying tasks, and also in vocal imitation of nonexperimental stimuli, three participants have shown improvements when comparing to pretest. Results confirm that teaching can improve important rehabilitation skills for individuals with prelingual deafness who are using cochlear implant. Furthermore, results suggest that some tasks might be more appropriate for learning effectiveness.